If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 89 + -5x = 7x + 12 Reorder the terms: 89 + -5x = 12 + 7x Solving 89 + -5x = 12 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 89 + -5x + -7x = 12 + 7x + -7x Combine like terms: -5x + -7x = -12x 89 + -12x = 12 + 7x + -7x Combine like terms: 7x + -7x = 0 89 + -12x = 12 + 0 89 + -12x = 12 Add '-89' to each side of the equation. 89 + -89 + -12x = 12 + -89 Combine like terms: 89 + -89 = 0 0 + -12x = 12 + -89 -12x = 12 + -89 Combine like terms: 12 + -89 = -77 -12x = -77 Divide each side by '-12'. x = 6.416666667 Simplifying x = 6.416666667
| 49x^2-4y^2= | | 2x-5=7+x | | 36x^2-169= | | 4r-8+7-6n=-9 | | 8x^2-13x+5= | | 10x^2+33x+9= | | 6x^2-x-5= | | 7x^2-45x+18= | | 7x^2-25x+12= | | x^10+5x^7+2x^2-x+2=0 | | 2x^2-11x-6= | | 4x+7=x+2 | | 10x+9=69 | | 12k-[4k+(-1+5k)]= | | 1*3+8*9= | | 2(t-3)-3(t-2)=t+8 | | 7x^2+23x+6= | | 0.7x^2-4.2x-0.7=0 | | 2x^2+11x+5= | | 3x^2+16x+5= | | 7x^2+32x+16= | | 86-4x=32x+22 | | 2x^2-11x+5= | | 12-10x=212-45x | | 2x+5=-25-8x | | 13x+12x+3=12 | | 7x^2-8x+1= | | 3l+80=5l | | 4x-2=11x-65 | | 5x+30=12x-26 | | 6x^3-4x^2+8x+2= | | 7p^2+8p+1=0 |